Integrating Writing Process with Quantum Learning Framework in English Language Teaching - Irfan Masrur; Enny Irawati; Gunadi Harry Sulistyo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: Writing with its complexity might make English language teaching more challenging for most English teachers to help learners facing difficulties in writing. Many students in any research report usually have problems in finding ideas to write and constructing sentences. This study was initially intended to solve those kinds of problem. The integration of writing process with Quantum Learning framework was the strategy implemented in this study. The result showed that the integration of writing process with Quantum Learning framework could make students’ writing better and enable the students to actively participate during the teaching and learning process.Abstrak: Rumitnya menulis membuat pengajaran bahasa Inggris lebih menantang bagi beberapa guru bahasa Inggris untuk membantu para pesertadidik menghadapi kesulitan dalam menulis. Dalam setiap laporan penelitian, beberapa siswa biasanya memiliki masalah dalam menemukan ide untuk menulis dan menyusun kalimat. Penelitian ini dimaksudkan untuk memecahkan masalah-masalah tersebut. Integrasi proses menulis dengan Quantum Learning adalah strategi yang diterapkan dalam penelitian ini. Hasil penelitian menunjukkan bahwa integrasi proses menulis dengan Quantum Learning dapat membuat tulisan siswa lebih baik dan memungkinkan siswa untuk berpartisipasi aktif selama proses belajar mengajar.